Extraction of essential oil from indigenous herb Physalis Minima Linn using microwave assisted extraction: article - Mohd Kamaruzaman, Muhammad Faez; Che Radzi, Nurhaslina (2019)
Essential oil is a kind of remedy that is originated from various part of plants. One of them is Physalis Minima L. that is beneficial to human health yet been ignored by Malaysian. There are few research related to the extraction of essential oil from Physalis Minima L. However, most of these research use soxhlet extraction method. This method is associated with issues related to hazard when using petroleum-based solvent. Thus, microwave assisted extraction is proposed to be used as it should be a greener extraction technique. The objective of this research is to study the effect of extraction time, liquid-to-solid ratio and microwave power to the extraction yield of oil from Physalis minima L. using microwave assisted extraction (MAE). Three parameters were investigated in this study namely extraction time, liquid-to-solid ratio and microwave power. The optimum condition of MAE of Physalis minima L. are 12 minutes for duration of extraction time, 12 mL/g for liquid-to-solid ratio and 630 for microwave power. The maximum yield of essential oil at this optimum condition are 21 %. The essential oil at this optimum condition were analyzed by using GC-MS. The highest constituent was 4,5-Dichloro-ortho-phenylenediamine (24.0657), Diethyl Phthalate (24.0864) and Phthalic acid, ethyl 2-pentyl ester (24.0914) with percentage of 4.0970 %. Based on research, it can be concluded that Physalis minima L. has some health beneficial as the isolated component is confirmed to exhibits beneficial health like antimicrobial, anticancer and anti-toxic agent.